A 2-Year Randomized Controlled Trial of Human Caloric Restriction: Feasibility and Effects on Predictors of Health Span and Longevity - Ravussin, Eric; Redman, Leanne M; Rochon, James; Das, Sai Krupa; Fontana, Luigi; Kraus, William E; Romashkan, Sergei; Williamson, Donald A; Meydani, Simin N; Villareal, Dennis T; Smith, Steven R; Stein, Richard I; et al. (The journals of gerontology. Series A, Biological sciences and medical sciences, 2015)
Caloric restriction (CR), energy intake reduced below ad libitum (AL) intake, increases life span in many species. The implications for humans can be clarified by randomized controlled trials of CR. To determine CR's feasibility, safety, and effects on predictors of longevity, disease risk factors, and quality of life in nonobese humans aged 21-51 years, 218 persons were randomized to a 2-year intervention designed to achieve 25% CR or to AL diet. Outcomes were change from baseline resting metabolic rate adjusted for weight change ("RMR residual") and core temperature (primary); plasma triiodothyronine (T3) and tumor necrosis factor-α (secondary); and exploratory physiological and psychological measures. Body mass index averaged 25.1 (range: 21.9-28.0 kg/m(2)). Eighty-two percent of CR and 95% of AL participants completed the protocol. The CR group achieved 11.7±0.7 %CR (mean ± standard error) and maintained 10.4±0.4% weight loss. Weight change in AL was negligible. RMR residual decreased significantly more in CR than AL at 12 months (p = .04) but not 24 months (M24). Core temperature change differed little between groups. T3 decreased more in CR at M12 and M24 (p < .001), while tumor necrosis factor-α decreased significantly more only at M24 (p = .02). CR had larger decreases in cardiometabolic risk factors and in daily energy expenditure adjusted for weight change, without adverse effects on quality of life. Sustained CR is feasible in nonobese humans. The effects of the achieved CR on correlates of human survival and disease risk factors suggest potential benefits for aging-related outcomes that could be elucidated by further human studies.